Od zabawy lalkami do zabawy słowami — tomiki wierszy dla dzieci Pawła Beręsewicza - Zabawa, Krystyna (Paidia i Literatura, 2020)
The paper includes the analyses of three books of poems by Paweł Beręsewicz: Lalki Dorotki [Dorotka’s dolls] (2004), Czy pisarzom burczy w brzuchu? [Do writers’ stomachs grumble?] (2009) oraz Złota jedenastka… [The golden eleven…] (2018). The author studies language, composition, the voice and characters creation, as well as the main idea of the three books, also paying attention to illustrations. She reconstructs the status of a speaker and a recipient, and their relationship (i.e. an adult–child relationship). It is also an attempt to place Beręsewicz’s books of poems in the context of his stories and novels.